Characteristic Analysis of 8kW Class High-Speed Permanent Magnet Synchronous Motor - Bang, Tae-Kyoung; Shin, Kyung-Hun; Lee, Jeong-In; Lee, Hoon-Ki; Cho, Han-Wook; Park, Pan-Gun; Choi, Jang-Young (International Journal of Engineering and Technology, 2018)
Background/Objectives: This paper deals with characteristic analysis of High-Speed Permanent Magnet Synchronous Machine (High-Speed PMSM) for air-blower by using FEM (Finite Element Method) S/W tools and analytical method.Methods/Statistical analysis: The High-Speed PMSM need the protective tube with non-magnetic materials that protect the scattering of permanent magnet, for preventing the damage of the High-Speed PMSM, it is necessary that analyzed about mechanical analysis.Findings: The results of the stress analytical method are compared with the results of FEM analysis that validated the analytical method of stress analysis. Based on the results of the analysis, an analytical model was fabricated. Through the experiments, the presence of rotor breakage was examined and the performance was measured.Improvements/Applications: The analysis methods presented in this paper could be applied to characteristic analysis of the high-speed permanent magnet machine